(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Ring theory is one of the parts of the abstract algebra that has been comprehensively utilized in images. Be that as it may, ring theory has not been connected with picture segmentation. In this paper, we propose another list of likeness among images utilizing __ rings and the entropy function. This new file was connected as another ceasing standard to the Mean Shift Iterative Algorithm with the objective to achieve a superior segmentation. An investigation on the execution of the algorithm with this new halting standard is completed. Though ring theory and class theory at first pursued diverse bearings it turned out during the 1970s – that the study of functor classifications additionally uncovers new angles for module theory.